1995
DOI: 10.1103/physreve.52.5297
|View full text |Cite
|
Sign up to set email alerts
|

Lattice-gas model for collective biological motion

Abstract: A simple self-driven lattice-gas model for collective biological motion is introduced. We find weakly first order phase transition from individual random walks to collective migration. A meanfield theory is presented to support the numerical results.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 18 publications
1
56
0
Order By: Relevance
“…The above results caused a well-deserved stir and prompted a large number of studies at various levels [3,4,6,7,8,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. In particular, two of us showed that the onset of collective motion is in fact discontinuous [38], and that the original conclusion of Vicsek et al was based on numerical results obtained at too small sizes [5,9].…”
Section: Introductionmentioning
confidence: 97%
“…The above results caused a well-deserved stir and prompted a large number of studies at various levels [3,4,6,7,8,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. In particular, two of us showed that the onset of collective motion is in fact discontinuous [38], and that the original conclusion of Vicsek et al was based on numerical results obtained at too small sizes [5,9].…”
Section: Introductionmentioning
confidence: 97%
“…The only rule is that, at each time step, every particle approximates, with some uncertainty, the average direction of motion of the particles within its neighborhood of radius R. This model exhibits spontaneous self-organization; by decreasing the noise parameter, the system undergoes a kinetic phase transition from a disordered state to an ordered one where all the particles move approximately in the same direction. Due its simplicity and analogy with biological systems comprised of many, locally interacting particles, the SPP model soon became a reference model for the flocking behavior of organisms [13,14,15,16,17,18,19,20,21,22,23].…”
Section: Inroductionmentioning
confidence: 99%
“…The external state of each individual has q states as in Potts model which is corresponding to q moving directions. The external state is similar to the definition of the individuals in the lattice gas model developed by Csahók et al [18]. But in our model, the rules of interaction between the two individuals are controlled by their internal state, i.e., there is no interaction if and only if both individuals are in non-excited state.…”
Section: Discussionmentioning
confidence: 86%